Preparation method of high-purity alumina thermal spraying powder for insulating ceramic bearing

By using thermal spraying technology and flame melting on insulated ceramic bearings to form a uniform coating and performing heat treatment, the problems of uneven surfaces and inconsistent thicknesses of ceramic bearings are solved, and the performance and service life of the bearings are improved.

CN119843203AActive Publication Date: 2025-04-18JINZHOU JINJIANG SPRAYING MATERIAL CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202311339936.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-17
Publication Date
2025-04-18
Estimated Expiration
2043-10-17

AI Technical Summary

Technical Problem

In the prior art, most of the preparation methods of high-purity alumina thermal spray powder for insulated ceramic bearings cannot ensure the uniformity of the coating, resulting in uneven surfaces or inconsistent thicknesses of ceramic bearings, affecting bearing performance, increasing the unqualified rate and production costs.

Method used

By selecting alumina powder with an average particle size between 1 and 50 microns and mixing with flowability improvers and binders, the powder is sprayed onto the preheated ceramic bearing surface using a thermal spray device, melted with flame and formed a uniform coating, followed by additional heat treatment to improve the density and wear resistance of the coating.

Benefits of technology

The flatness and consistency of the surface of ceramic bearings is achieved, which reduces the unqualification rate and production costs, and improves the electrical insulation performance, wear resistance and corrosion resistance of the bearings, and extends the service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004496944140000091
    Figure BDA0004496944140000091
Patent Text Reader

Abstract

The invention relates to the technical field of coating and surface treatment, and discloses a preparation method of high-purity aluminum oxide thermal spraying powder for an insulating ceramic bearing, which comprises the following steps: selecting aluminum oxide powder with the average particle size of 1-50 microns, and preparing the aluminum oxide powder by a chemical method or a physical method to ensure that the purity and the particle size distribution of the aluminum oxide powder meet the requirements; and 2, the aluminum oxide powder prepared in the step 1 in advance is mixed with a fluidity improver, and the fluidity improver is an organic compound and aims at improving the fluidity of the aluminum oxide powder so that the aluminum oxide powder can be better sprayed to the surface of the ceramic bearing. Compressed air or gas is transmitted through the spraying device to spray powder to the surface, uniform covering and tight attachment are ensured, meanwhile, high-temperature flames are used for melting the powder and spraying the powder to the surface of the bearing, a uniform coating is formed, and therefore the reject ratio of the ceramic bearing is reduced, and the production cost is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of coating and surface treatment, in particular to a method for preparing high-purity alumina thermal spray powder for insulating ceramic bearings. Background Art

[0002] The preparation of high-purity alumina thermal spray powder for insulating ceramic bearings usually involves a high-temperature thermal spray process, in which high-purity alumina powder is heated to a molten state and then sprayed onto the bearing surface through a gas or powder spray gun. This technology helps improve the performance of insulating ceramic bearings, making them perform well in electrical, mechanical and high-temperature environments.

[0003] Most of the existing methods for preparing high-purity alumina thermal spray powder for insulating ceramic bearings cannot ensure the uniformity of the coating, resulting in an uneven surface or inconsistent thickness of the ceramic bearings, which affects the performance of the bearings and causes the bearings to rotate less smoothly, thereby increasing the failure rate of ceramic bearings and increasing production costs. Summary of the invention

[0004] In view of the shortcomings of the prior art, the present invention provides a method for preparing high-purity alumina thermal spray powder for insulating ceramic bearings, which solves the problem that most of the preparation methods of high-purity alumina thermal spray powder in the prior art cannot ensure the uniformity of the coating, thereby affecting the performance of the bearings, increasing the failure rate of ceramic bearings, and increasing the production cost.

[0005] To achieve the above objectives, the present invention is implemented by the following technical scheme: A method for preparing high-purity alumina thermal spray powder for insulating ceramic bearings, comprising the following steps:

[0006] Step 1: Select alumina powder with an average particle size between 1 and 50 microns. Alumina powder can be prepared by chemical or physical methods to ensure that its purity and particle size distribution meet the requirements;

[0007] Step 2: mixing the aluminum oxide powder prepared in step 1 with a fluidity improver, wherein the fluidity improver is an organic compound that is intended to improve the fluidity of the aluminum oxide powder so that it can be sprayed on the surface of the ceramic bearing;

[0008] Step 3: Add a binder to the alumina powder mixed in step 2, and stir and mix using a stirring device. The binder is an organic resin, which is used to bond the mixture to the surface after spraying;

[0009] Step 4: Use a thermal spray device to spray the powder mixed in step 3 onto the pre-heated insulating ceramic bearing surface by delivering compressed air or gas to ensure uniform coverage and close adhesion;

[0010] Step 5: During the thermal spraying process in step 4, a burner is used to provide fuel and an oxidant to generate a flame. The flame melts the powder and sprays it onto the bearing surface to form a uniform coating. The volume ratio of the combustion gas to the oxidant is 1:1.

[0011] Step 6: After the coating in step 5 is formed, an additional heat treatment step is performed. This additional heat treatment step is to place the coating in a high temperature environment and sinter it for 15 to 30 minutes to improve the density, mechanical properties and wear resistance of the coating, thereby improving the performance of the insulating ceramic bearing;

[0012] Step 7: After preparation, the coating has insulating properties and is suitable for the application of insulating ceramic bearings. This coating can improve the electrical insulation performance, wear resistance and corrosion resistance of the bearings, and effectively extend the service life of the bearings.

[0013] Preferably, the chemical method in step 1 is to convert appropriate raw materials into aluminum oxide powder through a chemical reaction, and the specific steps are as follows:

[0014] S1: react the aluminum source with alkaline solution to generate aluminum hydroxide precipitate

[0015] S2: The precipitate is washed and filtered to remove impurities;

[0016] S3: The aluminum hydroxide precipitate is dried and calcined to be converted into aluminum oxide powder. The aluminum oxide powder at this time is generally a high-purity aluminum oxide powder with a purity of more than 99.9%.

[0017] Preferably, the aluminum source is aluminate, such as aluminum nitrate or aluminum sulfate, the alkaline solution is sodium hydroxide, and the aluminum oxide powder prepared by the chemical method needs to treat waste liquid and waste gas to ensure the quality of the obtained powder.

[0018] Preferably, the physical method in step 1 is to convert the raw material into alumina powder through a physical process without involving a chemical reaction, and the specific steps are as follows:

[0019] S1: First, high-purity aluminum metal or aluminum oxide powder is placed into a high-temperature furnace and then transported by a gas stream;

[0020] S2: At high temperatures, the raw materials undergo physical changes and eventually form alumina powder.

[0021] Preferably, the gas is hydrogen or nitrogen, and the alumina powder prepared by the physical method does not involve chemical reaction, so there is no need to treat waste liquid and waste gas.

[0022] Preferably, the fluidity improver in step 2 is tested at different binder concentrations, and the alumina powder with the best concentration for fluidity and adhesion is selected based on the test results. At the same time, the samples of each concentration are subjected to adhesion strength test, hardness test and microstructure observation steps, and based on the test results, the amount of binder is further adjusted until the desired coating performance is achieved and the optimal amount of alumina powder is obtained.

[0023] Preferably, the ratio of combustion gas and oxidant in step five is achieved by mixing the combustion gas and oxidant together through a mixing device when the combustion gas and oxidant are supplied to the reactor separately to ensure that their ratio is uniform and the desired chemical reaction conditions are achieved. At the same time, during the chemical reaction, the supply ratio of combustion gas and oxidant can be adjusted in time by monitoring and controlling parameters such as temperature, pressure, and residual oxidant in the reactor. The gas phase composition or other key parameters in the reactor are measured by sensors, and this information is compared with the desired ratio. Therefore, according to these feedback signals, the supply of combustion gas and oxidant is adjusted to maintain the desired ratio.

[0024] Preferably, the binder in step three is epoxy resin, and after the epoxy resin is mixed with alumina powder, chemical reaction, physical crosslinking and thermal curing are carried out to form a solid structure, providing good bonding performance.

[0025] Preferably, the preheating method of the insulating ceramic bearing surface preheated in step 4 includes constant temperature furnace heating, infrared heating, laser heating and resistance heating.

[0026] Preferably, the fluidity improver includes solvents, plasticizers, surfactants, polymer additives and acid anhydrides.

[0027] The present invention provides a method for preparing high-purity alumina thermal spray powder for insulating ceramic bearings. It has the following beneficial effects:

[0028] 1. The present invention transmits compressed air or gas through a spraying device to spray powder onto the surface to ensure uniform coverage and close adhesion. At the same time, a burner is used to provide fuel and an oxidant to generate a flame. The flame melts the powder and sprays it onto the bearing surface to form a uniform coating. Therefore, the flatness or uniform thickness of the ceramic bearing surface can be ensured, thereby reducing the failure rate of the ceramic bearing and reducing the production cost.

[0029] 2. The present invention places the formed coating in a high temperature environment and sintering it for a certain period of time, thereby completing the heat treatment of the coating after formation, thereby improving the density and wear resistance of the coating, thereby improving the performance of the insulating ceramic bearing. DETAILED DESCRIPTION

[0030] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0031] Embodiment 1:

[0032] The embodiment of the present invention provides a method for preparing high-purity alumina thermal spray powder for insulating ceramic bearings, comprising the following steps:

[0033] Step 1: Select alumina powder with an average particle size between 1 and 50 microns. Alumina powder can be prepared by chemical or physical methods to ensure that its purity and particle size distribution meet the requirements;

[0034] Step 2: mixing the aluminum oxide powder prepared in step 1 with a fluidity improver, wherein the fluidity improver is an organic compound that is intended to improve the fluidity of the aluminum oxide powder so that it can be sprayed on the surface of the ceramic bearing;

[0035] Step 3: Add a binder to the alumina powder mixed in step 2, and stir and mix using a stirring device. The binder is an organic resin, which is used to bond the mixture to the surface after spraying;

[0036] Step 4: Use a thermal spray device to spray the powder mixed in step 3 onto the pre-heated insulating ceramic bearing surface by delivering compressed air or gas to ensure uniform coverage and close adhesion;

[0037] Step 5: During the thermal spraying process in step 4, a burner is used to provide fuel and an oxidant to generate a flame. The flame melts the powder and sprays it onto the bearing surface to form a uniform coating. The volume ratio of the combustion gas to the oxidant is 1:1.

[0038] Step 6: After the coating in step 5 is formed, an additional heat treatment step is performed. This additional heat treatment step is to place the coating in a high temperature environment and sinter it for 20 minutes to improve the density, mechanical properties and wear resistance of the coating, thereby improving the performance of the insulating ceramic bearing;

[0039] Step 7: After preparation, the coating has insulating properties and is suitable for the application of insulating ceramic bearings. This coating can improve the electrical insulation performance, wear resistance and corrosion resistance of the bearings, and effectively extend the service life of the bearings.

[0040] The chemical method in step 1 is to convert appropriate raw materials into alumina powder through chemical reactions. The specific steps are as follows:

[0041] S1: react the aluminum source with alkaline solution to generate aluminum hydroxide precipitate

[0042] S2: The precipitate is washed and filtered to remove impurities;

[0043] S3: The aluminum hydroxide precipitate is dried and calcined to be converted into aluminum oxide powder. The aluminum oxide powder at this time is generally a high-purity aluminum oxide powder with a purity of more than 99.9%.

[0044] The aluminum source is aluminate, such as aluminum nitrate or aluminum sulfate, and the alkaline solution is sodium hydroxide. The alumina powder prepared by the chemical method requires the treatment of waste liquid and waste gas to ensure the quality of the obtained powder.

[0045] The physical method in step 1 is to convert the raw materials into alumina powder through a physical process without involving a chemical reaction. The specific steps are as follows:

[0046] S1: First, high-purity aluminum metal or aluminum oxide powder is placed into a high-temperature furnace and then transported by a gas stream;

[0047] S2: At high temperatures, the raw materials undergo physical changes and eventually form alumina powder.

[0048] The gas is hydrogen or nitrogen. The alumina powder prepared by physical method does not involve chemical reaction, so there is no need to treat waste liquid and waste gas.

[0049] In step 2, the fluidity improver is tested at different binder concentrations, and the alumina powder with the best fluidity and adhesion concentration is selected based on the test results. At the same time, the samples of each concentration are subjected to adhesion strength tests, hardness tests and microstructure observations. Based on the test results, the amount of binder is further adjusted until the desired coating performance is achieved and the optimal amount of alumina powder is obtained.

[0050] The detailed steps of testing the fluidity improver with different binder concentrations are as follows:

[0051] S1: From initial references or experience, select an initial binder concentration that can serve as a starting point for testing. This initial concentration may be based on previous similar applications or recommendations.

[0052] S2: preparing a series of samples, each sample having a different binder concentration, according to the selected initial concentration, by mixing alumina powder and binder and forming them into samples under appropriate conditions;

[0053] S3: Use an appropriate rheometer or flow testing equipment to measure the flowability of each sample. The flowability test can be used to evaluate the flow characteristics of powder particles at different binder concentrations.

[0054] S4: Adhesion test was performed on each sample to evaluate the effect of binder concentration on powder adhesion;

[0055] S5: Record the data of fluidity and adhesion tests, including the binder concentration and related test results of each sample;

[0056] S6: repeating steps 2 to 5, using different binder concentration ranges to cover a wider concentration range;

[0057] S7: Determine the optimal binder concentration range based on the test results and data analysis.

[0058] In step five, the ratio of combustion gas and oxidant is achieved by supplying the combustion gas and oxidant separately to the reactor and then mixing the two together through a mixing device to ensure that their ratio is uniform and the desired chemical reaction conditions are achieved. At the same time, during the chemical reaction, the supply ratio of combustion gas and oxidant can be adjusted in time by monitoring and controlling parameters such as temperature, pressure, and residual oxidant in the reactor. The gas phase composition or other key parameters in the reactor are measured by sensors, and this information is compared with the desired ratio. Therefore, based on these feedback signals, the supply of combustion gas and oxidant is adjusted to maintain the desired ratio.

[0059] The binder in step 3 is epoxy resin. After the epoxy resin is mixed with alumina powder, chemical reaction, physical cross-linking and thermal curing are carried out to form a solid structure, providing good bonding performance;

[0060] Specifically, a chemical reaction is a process that changes the structure of a molecule by forming or breaking chemical bonds. In the process of forming a strong structure, chemical reactions are usually introduced, such as polymerization reactions, in which monomer molecules are linked together by covalent bonds to form larger molecules or polymers. These covalent bonds are very strong, so a strong chemical structure can be formed in the material; physical crosslinking is a process in which the structure is formed in the material by physical forces other than covalent bonds. These physical forces include van der Waals forces, hydrogen bonds, electrostatic interactions, etc. between molecules. When these interactions exist between molecules, they can attract each other and form a strong network structure. For example, many elastomeric materials, such as rubber, are formed by physical crosslinking, where the crosslinking points between molecules are caused by physical attraction; thermal curing is the process of heating a material to force it to form a strong structure. Typically, this involves heating the material to activate a chemical reaction or rearrange the molecules, thereby introducing crosslinks or crosslinking points in the material. Once the material has been thermally cured, it will have higher hardness and heat resistance. Thermosetting resins, such as epoxy resins, are common examples. They need to be heated to form a strong structure.

[0061] The preheating method of the insulating ceramic bearing surface preheated in step 4 includes constant temperature furnace heating, infrared heating, laser heating and resistance heating;

[0062] Specifically, constant temperature furnace heating: the insulating ceramic bearing is placed in a constant temperature furnace and heated evenly at a predetermined temperature. This method is suitable for situations where high temperature accuracy and stability are required. The appropriate heating time and temperature can be selected according to the size of the bearing and the heat treatment requirements; infrared heating: an infrared heating lamp or an infrared heater is used to heat the surface of the insulating ceramic bearing. Infrared heating can achieve rapid heating and local heating, which is suitable for heating needs of small sizes and specific areas; laser heating: a laser heating device is used to locally heat the surface of the insulating ceramic bearing. Laser heating has high energy density and precise energy control, and is suitable for situations where local pre-heating is required; resistance heating: a resistance wire or a resistance sheet is placed on the insulating ceramic bearing and powered on for heating. Resistance heating can provide uniform heating and controllable heating temperature, which is suitable for bearings of larger sizes or complex shapes.

[0063] Flow improvers include solvents, plasticizers, surfactants, polymer additives and anhydrides;

[0064] Specifically, solvents: adding solvents is one of the most common methods to improve fluidity. Solvents can reduce the viscosity of coatings or liquids, making them easier to apply or spray. Common organic solvents include acetone, dimethylformamide, methanol, ethanol, etc. Plasticizers: Plasticizers are a class of organic compounds that enhance the plasticity and fluidity of liquids. These compounds are usually compatible with polymers and improve the processing properties of materials. For example, phthalate plasticizers are commonly used in polyvinyl chloride resins; Surfactants: adding surfactants can reduce the surface tension of liquids and improve their wettability and permeability, which helps to form a uniform coating on the substrate. The choice of surfactant depends on the chemical properties of the system, such as non-ionic, ionic or mixed surfactants; Polymer additives: Some high molecular weight polymers, such as polyethylene ether and polypropylene ether, can be used as fluidity improvers. They form macromolecular chains in liquids, reduce friction, and improve fluidity; Anhydrides: Anhydride compounds, such as phenolic anhydride, can be used as fluidity improvers in coatings and paints. They react with hydroxyl groups to form ester bonds, change the molecular structure, and thus reduce viscosity.

[0065] Embodiment 2:

[0066] To distinguish the first embodiment from the second embodiment, three ceramic bearings are used as in the first embodiment, and the coating is evenly applied on the ceramic bearings. The ceramic bearings evenly coated with the coating are then placed in a high-temperature furnace and sintered for 15 minutes, 20 minutes and 30 minutes respectively, to obtain Table 1.

[0067] Embodiment three:

[0068] In order to distinguish between Example 1 and Example 2, a ceramic bearing identical to Example 1 is treated with the same method as Example 1 but without performing the heat treatment step of step 6 to obtain an insulating ceramic bearing, which is compared with the insulating ceramic bearing obtained by the method in Example 1 to obtain Table 2, in which the density test is reflected by the microhardness. The greater the microhardness, the better the density. The microhardness test is performed using the same microhardness testing instrument to test the insulating ceramic bearings of Example 1 and Example 2. The wear resistance test is reflected by the wear depth. The deeper the wear depth, the worse the wear resistance.

[0069]

[0070] Table 1

[0071] Embodiment 1 Embodiment 3 Microhardness / MPa 865 534 Wear depth / μm 43 236

[0072] Table 2

[0073] Conclusion: From the data in Table 1 and Table 2, it can be concluded that the method in Example 1 can effectively improve the qualified rate, density and wear resistance.

[0074] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing high-purity alumina thermal spray powder for insulating ceramic bearings, characterized in that: The following steps are involved: Step 1: Select alumina powder with an average particle size between 1 and 50 microns. Alumina powder can be prepared by chemical or physical methods to ensure that its purity and particle size distribution meet the requirements; Step 2: mixing the aluminum oxide powder prepared in step 1 with a fluidity improver, wherein the fluidity improver is an organic compound that is intended to improve the fluidity of the aluminum oxide powder so that it can be sprayed on the surface of the ceramic bearing; Step 3: Add a binder to the alumina powder mixed in step 2, and stir and mix using a stirring device. The binder is an organic resin, which is used to bond the mixture to the surface after spraying; Step 4: Use a thermal spray device to spray the powder mixed in step 3 onto the pre-heated insulating ceramic bearing surface by delivering compressed air or gas to ensure uniform coverage and close adhesion; Step 5: During the thermal spraying process in step 4, a burner is used to provide fuel and an oxidant to generate a flame. The flame melts the powder and sprays it onto the bearing surface to form a uniform coating. The volume ratio of the combustion gas to the oxidant is 1:

1. Step 6: After the coating in step 5 is formed, an additional heat treatment step is performed. This additional heat treatment step is to place the coating in a high temperature environment and sinter it for 15 to 30 minutes to improve the density, mechanical properties and wear resistance of the coating, thereby improving the performance of the insulating ceramic bearing; Step 7: After preparation, the coating has insulating properties and is suitable for the application of insulating ceramic bearings. This coating can improve the electrical insulation performance, wear resistance and corrosion resistance of the bearings, and effectively extend the service life of the bearings.

2. The method for preparing a high-purity alumina thermal spray powder for insulating ceramic bearings according to claim 1, characterized in that: The chemical method in step 1 is to convert appropriate raw materials into aluminum oxide powder through chemical reaction, and the specific steps are as follows: S1: react the aluminum source with alkaline solution to generate aluminum hydroxide precipitate S2: The precipitate is washed and filtered to remove impurities; S3: The aluminum hydroxide precipitate is dried and calcined to be converted into aluminum oxide powder. The aluminum oxide powder at this time is generally a high-purity aluminum oxide powder with a purity of more than 99.9%.

3. The method for preparing a high-purity alumina thermal spray powder for insulating ceramic bearings according to claim 2, characterized in that: The aluminum source is aluminate, such as aluminum nitrate or aluminum sulfate, the alkaline solution is sodium hydroxide, and the aluminum oxide powder prepared by the chemical method needs to treat waste liquid and waste gas to ensure the quality of the obtained powder.

4. The method for preparing a high-purity alumina thermal spray powder for insulating ceramic bearings according to claim 1, characterized in that: The physical method in step 1 is to convert the raw material into alumina powder through a physical process without involving a chemical reaction. The specific steps are as follows: S1: First, high-purity aluminum metal or aluminum oxide powder is placed into a high-temperature furnace and then transported by a gas stream; S2: At high temperatures, the raw materials undergo physical changes and eventually form alumina powder.

5. The method for preparing high-purity alumina thermal spray powder for insulating ceramic bearings according to claim 4, characterized in that: The gas is hydrogen or nitrogen, and the aluminum oxide powder prepared by the physical method does not involve chemical reaction, so there is no need to treat waste liquid and waste gas.

6. The method for preparing high-purity alumina thermal spray powder for insulating ceramic bearings according to claim 1, characterized in that: In step 2, the fluidity improver is tested at different binder concentrations, and the alumina powder with the best fluidity and adhesion concentration is selected based on the test results. At the same time, the adhesion strength test, hardness test and microstructure observation steps are also carried out on the samples of each concentration. Based on the test results, the amount of binder is further adjusted until the desired coating performance is achieved and the optimal amount of alumina powder is obtained.

7. The method for preparing high-purity alumina thermal spray powder for insulating ceramic bearings according to claim 1, characterized in that: In step five, the ratio of combustion gas and oxidant is obtained by mixing the combustion gas and oxidant together through a mixing device when the combustion gas and oxidant are supplied to the reactor separately to ensure that the ratio is uniform and the desired chemical reaction conditions are achieved. Meanwhile, during the chemical reaction, the supply ratio of combustion gas and oxidant can be adjusted in time by monitoring and controlling parameters such as temperature, pressure, and residual oxidant in the reactor. The gas phase composition or other key parameters in the reactor are measured by sensors, and this information is compared with the desired ratio. Therefore, according to these feedback signals, the supply of combustion gas and oxidant is adjusted to maintain the desired ratio.

8. The method for preparing high-purity alumina thermal spray powder for insulating ceramic bearings according to claim 1, characterized in that: The adhesive in step three is epoxy resin. After the epoxy resin is mixed with alumina powder, chemical reaction, physical crosslinking and thermal curing are carried out to form a solid structure, providing good bonding performance.

9. The method for preparing high-purity alumina thermal spray powder for insulating ceramic bearings according to claim 1, characterized in that: The preheating methods of the insulating ceramic bearing surface preheated in step 4 include constant temperature furnace heating, infrared heating, laser heating and resistance heating.

10. The method for preparing high-purity alumina thermal spray powder for insulating ceramic bearings according to claim 1, characterized in that: The fluidity improver includes solvents, plasticizers, surfactants, polymer additives and acid anhydrides.

Citation Information

Patent Citations

  • Insulating thermal conductive composite ceramic powder, preparation method and application thereof and insulating thermal conductive coating

    CN109369158A

  • Liquid ceramic spraying preparation method for tableware

    CN109456039A

  • Spray type preparation method of liquid ceramic for mobile phone shell

    CN109487194A

  • Thermal spraying material

    JP1996290977A

  • Binder system for use in the injection molding of sinterable powders and molding compound containing the binder system

    US5380179A